AB1084 Treatment Patterns and Retention in an Inception Cohort of 309 RA Patients. (10th June 2014) - Studenic, P.; Smolen, J.S.; Alasti, F.; Aletaha, D.
Abstract : Background: The last decade brought major advances in the available treatment choices for rheumatoid arthritis (RA) patients. Also, new treatment algorithms propose rapid therapeutic adaptations, and, if needed, a quick step-up to biological DMARDs in patients at risk for bad outcome. Objectives: We aimed to establish the temporal trends in disease modifying antirheumatic drug (DMARD) applications in the 21st century. Methods: Beginning in 2001, we identified an inception cohort of patients who had at least 3 complete follow-up visits, and received a DMARD therapy for at least one month. We divided DMARDs into 5 groups and used survival analysis, cox regression and comparative analyses. Results: We identified 309 patients who fulfilled inclusion criteria (75% female, 56% rheumatoid factor positive, median symptom duration 0.8 (0.4-2.1) years; median SDAI was 17.7 (9.8-30.0). 69% of the patients showed moderate to high clinical disease activity at start of their first treatment. As first treatment, 294 patients (95%) received a conventional synthetic (cs) DMARD strategy, in 77.3% of patients this was methotrexate (MTX), in 8.7% salazopyrine and in 6.5% leflunomide. As second treatment after MTX most patients received either another csDMARD (47%) or a biologic (b) DMARD (39%). Biological DMARDs were used increasingly after failure of increasing numbers of csDMARD therapies (Table). Median retention of the first five treatment segments were 35.7 months (95% confidence interval: 20.1-51.3), 25.2 (16.5-33.9), 14.2 (4.9-23.5), 14.4 (11.4-17.4), 10 (6.2-13.9) months; the rate of censoring (still ongoing therapies) was between 44% and 48% in the first 3 segments and 26% and 32% for segments 4 and 5. In analyses of all treatment segments, csDMARDs (30.7 months; 22.8-38.6) and tumor necrosis factor alpha-inhibitor (TNFi)-combinations (29.4; 14.8-44.0) showed the highest retention rates, followed by combinational therapy of synthetic DMARDs (15.3; 2.4-28.2), non-TNFi-bDMARDs (13.5; 10.2-16.8) and biological-monotherapy (11.7; 1.9-21.5). When adjusting for number of previous treatment segments (p<0.001), the total observation period (p=0.61) and CDAI levels (p=0.03) at the respective treatment starts, TNFi bDMARDs showed the longest retention rates and csDMARDs and non-TNFi bDMARDs were very similar. After the first treatment course bDMARDs showed longer survival than csDMARDs (2nd segment: 22.6 vs. 39.1 p=0.087). Disease activity markers at baseline were not significantly different between different treatment segments, except for acute phase reactant levels, which decreased with each treatment course (p<0.001 for CRP; p=0.037 for ESR). With higher number of previous treatment courses, more patients were rheumatoid factor and ACPA positive. Conclusions: MTX and leflunomide are clearly dominating in early treatment phases, but already as a second treatment choice biological DMARDs are of significance and show longer retention rates. After each previous treatment the retention of the treatment course decreases significantly. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3812